An Analysis Of Reading Comprehension Questions In English Textbook " English For Iraq" According To Revised Bloom’s Taxonomy - et. al., Maha Nader Tayyeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to analyze reading comprehension questions available in the English textbook, namely, "English for Iraq" for 2nd intermediate grade based on the cognitive domain of Bloom's taxonomy. To reach this end, a mixed method of content analysis was performed. The sample of the study consisted of all reading comprehension questions found in the textbook where the researcher examined (282) questions. The instrument that was used to collect, list, and classify these questions according to their cognitive levels was a checklist based on Bloom's taxonomy. Then, the percentages of each level that appeared in each study unit were calculated. The results revealed the following: the highest percentage of the questions were remembering (49.65%), and understanding (36.52%), and less for the other levels, applying (2.48%), analyzing (4.26%), evaluating (6.38%), and finally, creating (0.71%). These results exposed that all the cognitive levels were covered by the reading comprehension questions. However, most of the questions were dominated by lower-levels of cognitive processes. This indicates that the above-mentioned textbook failed to engage learners in the questions requiring higher-order levels because of the imbalanced distribution among the six levels of the cognitive domain.